Influence of urban layout on crime incidence using UAV images - Yusuf Bicer; Shouraseni Sen Roy; Richard Grant; Christopher Mader; Amin Sarafraz (Spatial Information Research, 2025)
Urban design and layout significantly influence crime patterns and community safety. Our study examines the effects of local-level urban layout on crime incidence in Coral Gables, a planned, higher-income area in Miami-Dade County, Florida. We assess key environmental attributes, including streetlights, layout, and sidewalks. Our analysis incorporates crime data, UAV orthophotos, and site-specific factors [e.g., streetlight illumination and sidewalk accessibility] to reveal spatiotemporal crime patterns. These patterns exhibit clustering and spatial unevenness. Neighborhood variability, including walkable, accessible neighborhoods, water barriers, gated community seclusion, and perimeter zones bordering lower-income and mixed-use development, influences crime distribution. The impact of streetlights varied across the city, with greater illumination, particularly from residential areas, acting as a significant deterrent against criminal activity. The northern area of Coral Gables aligns with higher crime concentration. Sidewalk accessibility affects crime rates, highlighting the importance of pedestrian-friendly infrastructure. Multi-residential buildings exhibit higher crime rates. Our findings underscore the significance of thoughtful urban planning and granular insights into micro-spatial patterns, which can inform targeted safety enhancements within specific neighborhood locations. Based on the current crime landscape in Coral Gables, we identify exciting avenues for future research with practical implications for crime prevention.

A comprehensive mouse IBD database for the efficient localization of quantitative trait loci - Alessandra C.L. Cervino; Mark Gosink; Mohammad Fallahi; Bruce Pascal; Christopher Mader; Nicholas F. Tsinoremas (Mammalian Genome, 2006)